Syrians of today, Germans of tomorrow: the effect of initial placement on the political interest of Syrian refugees in Germany - Kassam, Kamal; Becker, Maria (Frontiers in Political Science, 2023)
Syrian nationals are not only the largest refugee group in Germany, but also the third largest group of foreigners living in Germany. The naturalization trend amongst this group has been very pronounced in the last two years and is expected to increase sharply in the coming years. However, little is known about their political interest in German politics. Given the importance of "political interest" as an indicator of social integration and future active citizenship, this paper aims to examine the extent to which Syrian refugees are interested in (German) politics and how local conditions at the time of arrival influence refugees' interest in German politics. We focus on three dimensions of the neighborhood context theory (social networks, economic situation, and political environment) in combination with traditional political participation theory. Our analysis is based on the nationally representative sample of refugees in Germany (IAB-BAMF-SOEP). Furthermore, we rely on the exogenous distribution of refugees across federal states, which can be used to credibly identify the effect of local characteristics on refugees' political interest. Our results show that Syrian refugees are less interested in politics compared to the German population. Their lack of political interest is also reflected in the abundance of party preference. In terms of initial placement, our key finding suggests that ethnic social network plays a significant role in boosting newly arrived refugees' interest in German politics. Moreover, the results show that rising unemployment amongst the foreign population is associated with an increase in political interest amongst Syrian refugees. We can also confirm that political context affects political motivational factors, as high political interest amongst the native population in Germany leads to a higher political interest amongst Syrian refugees. These results show that more attention needs to be paid to the integration of Syrian refugees and underline the need to reassess the efficiency of distribution policy for Syrian refugees.